Capillary haemangioma in a 13-year-old boy. (25th July 2013) - Haddad, Charles; Haddad-Lacle, Judella; Webb, Fern
Abstract : This case presents a 13-year-old boy who developed an unusual skin lesion on his chest that occurred after 2–3 weeks following a traumatic injury. The lesion was raised and bled easily. It was surgically removed via shave excision and treated with electrocautery. The patient healed with no recurrence and minimal scarring. Pathology determined the skin lesion to be a capillary haemangioma.